Transition from Primary to Secondary School Mathematics: Students’ Perceptions - Catherine Attard (SEAMEO Regional Centre for QITEP in Mathematics, 2012)
During a longitudinal case study on engagement in Australian middle school years mathematics, 20 students in their first year of secondary school in Western Sydney, New South Wales, were asked about their experiences of the transition to secondary school in relation to their experiences of mathematics teaching and learning. Changes and disruptions in teacher-student relationships were a major cause of concern. This was due to fewer opportunities for teacher-student interactions and a heavy usage of computer-based mathematics lessons during the first months of secondary school. Findings indicate that a strong pedagogical relationship is a critical foundation for sustained engagement in mathematics during the middle years.